Deposisi, karakterisasi sifat optik dan uji degradasi Db71 pada lapisan tipis Zno:Co konsentrasi tinggi - Ahmad Pradana; Heri Sutanto; Eko Hidayanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
A thin layer of ZnO:Co was deposited on a glass substrate using a spray coating method with the addition of Co doping variations of 5%, 10%, 15%, 20% and 25%. The ZnO:Co thin film is further used to degrade the Direct Blue 71 dye solution under sunlight irradiation. ZnO:Co solution was synthesized by dissolving Zinc acetate dehydrate (ZnAc) into isopropanol and then added monoethanolamine (MEA) and cobalt nitrate at room temperature with concentration of ZnAc 0.3M and molar ratio of MEA and ZnAc of 1:1. Then the stirred solution used a magnetic stirrer at a temperature of 70oC for 30 minutes to obtain a clear and homogeneous gel. Gel ZnO:Co is placed on a spray hole and then sprayed on a heated glass substrate at 400oC. The optical properties of the ZnO:Co coating were characterized using UV-Vis spectroscopy. The results showed that the addition of Co doping on a thin layer of ZnO resulted in an increasingly high absorbance in the Co doping sample at a concentration of 15%. In addition, the greater concentration of Co will decrease the value of the energy band gap. The results of photodegradation test of Direct Blue 71 dye solution on ZnO:Co photocatalyst were able to degrade dye by 16% of entire samples .Keywords: Photocatalyst, Thin film ZnO:Co, Spray Coating, Direct Blue 71